A scoping review of South Africa’s readiness to integrate mental health services into National Health Insurance - Thwala, Ntuthuko Ricardo; Mokoena-de Beer, Andile Glodin (Orapuh Journal, 2025)
South Africa's National Health Insurance (NHI) system has the potential to achieve universal health coverage and address healthcare inequities but faces barriers such as underfunding, inadequate infrastructure, and limited private sector engagement. This scoping review aimed to map existing evidence on South Africa's readiness to integrate mental health services into the NHI system and to identify facilitators and barriers to successful integration. Following Arksey and O'Malley's framework, the review involved searching multiple databases, namely PubMed, Scopus, Web of Science, EBSCOhost, PsycINFO, and Google Scholar, for studies published between 1 January 2015 and 31 March 2025. The search terms included: ("National Health Insurance" OR "NHI") AND ("Mental Health Services" OR "mental health integration" OR "mental healthcare") AND ("South Africa" OR "South African"). Eighteen studies met the inclusion criteria, comprising 17 scientific papers and 1 policy document. Thematic analysis revealed five key themes: (1) policy framework and governance challenges; (2) financing mechanisms and resource allocation gaps; (3) health system capacity constraints; (4) implementation barriers; and (5) stakeholder readiness issues. Critical challenges include fragmented governance, chronic underfunding, workforce shortages, infrastructure limitations, and persistent stigma, particularly in relation to mental health services. This review highlights key challenges and potential strategies for integrating mental health into NHI through coordinated policy implementation, adequate resourcing, and meaningful stakeholder engagement. Therefore, mental health should be included in NHI benefit packages. Further recommendations include expansion of the primary healthcare workforce, strengthening of health information systems, and incorporation of community-based care models.